Optimization of Clotrimazole Emulgel: Evaluating the Effects of Oil Type, Oil Concentration, and Gellant Type on Physico-Chemical Performance: Optimization of Clotrimazole Emulgel Formulation - Bahrami Zanjanbar, Dorsa; Khalili, Hasti; Didehvar, Kimia; Dabirsiaghi, Alireza; Zandkarimi, Majid (Iranian Journal of Pharmaceutical Sciences, 2025)
Fungal infections of the skin are prevalent worldwide, and effective treatment requires innovative drug delivery systems. Emulgel, a novel formulation, offers several advantages, including non-greasiness, stain-free properties, improved patient compliance (particularly for individuals with hairy skin), enhanced spreadability, increased stability, and controlled drug release. This study investigates using emulgel as a delivery system for hydrophobic drugs, specifically Clotrimazole, in a hydrophilic base. Nine emulgel formulations were evaluated, focusing on three key factors: polymer type (Carbomer 940, Hydroxypropyl Methylcellulose K4M (HPMC K4M)), or a combination of both), and the type and percentage of the oily phase (5% Paraffin, 5% Isopropyl Myristate, and 7.5% Isopropyl Myristate). Three formulations failed to meet the mechanical stability criteria, while six formulations demonstrated stability across all tests. Drug release rates were as follows: F1 (81.43%), F2 (76.87%), F3 (85.56%), F7 (91.56%), F8 (87.89%), and F9 (97.64%). Over six hours, a commercially available Clotrimazole cream (Pars Daroo Company) released 71.11% of its drug content. Formulation 9 is the most effective formula, incorporating 5% Paraffin and a blend of Carbomer 940 and HPMC, and it followed the zero-order kinetic model. The inclusion of Paraffin, compared to Isopropyl Myristate, enhanced drug release due to the lower solubility of Clotrimazole in Paraffin. The Carbomer 940 and HPMC combination also provided optimal viscosity, ensuring stability, ease of application, and controlled release. It has also been shown that increasing oil concentration increases the drug's loading capacity while its release decreases.